Improved electrochemical performance of Sr2Fe1.5Mo0.4Nb0.1O6−δ –Sm0.2Ce0.8O2−δ composite cathodes by a one-pot method for intermediate temperature solid oxide fuel cells. (30th January 2016) - Guan, Mengjie; Sun, Wang; Ren, Rongzheng; Fan, Qinghua; Qiao, Jinshuo; Wang, Zhenhua; Rooney, David; Feng, Jinsheng; Sun, Kening
Abstract: In this paper, Sr2 Fe1.5 Mo0.4 Nb0.1 O6−δ (SFMNb)−xSm0.2 Ce0.8 O2−δ (SDC) (x = 0, 20, 30, 40, 50 wt%) composite cathode materials were synthesized by a one-pot combustion method to improve the electrochemical performance of SFMNb cathode for intermediate temperature solid oxide fuel cells (IT-SOFCs). The fabrication of composite cathodes by adding SDC to SFMNb is conducive to providing extended electrochemical reaction zones for oxygen reduction reactions (ORR). X-ray diffraction (XRD) demonstrates that SFMNb is chemically compatible with SDC electrolytes at temperature up to 1100 °C. Scanning electron microscope (SEM) indicates that the SFMNb-SDC composite cathodes have a porous network nanostructure as well as the single phase SFMNb. The conductivity and thermal expansion coefficient of the composite cathodes decrease with the increased content of SDC, while the electrochemical impedance spectra (EIS) exhibits that SFMNb-40SDC composite cathode has optimal electrochemical performance with low polarization resistance ( R p ) on the La0.9 Sr0.1 Ga0.8 Mg0.2 O3 electrolyte. The R p of the SFMNb-40SDC composite cathode is about 0.047 Ω cm 2 at 800 °C in air. A single cell with SFMNb-40SDC cathode also displays favorable discharge performance, whose maximum power density is 1.22 W cm −2 at 800 °C. All results indicate that SFMNb-40SDC composite material is a promising cathode candidate for IT-SOFCs. Highlights: Sr2 Fe1.5 Mo0.4 Nb0.1 O6−δ –Sm0.2 Ce0.8 O2−δ composite cathodes are prepared by a one-pot method. SFMNb-40SDC cathode exhibits the lowest R p of 0.047°Ωcm 2 at 800 °C. Single cell with SFMNb-40SDC cathode shows a maximum power density of 1.22 W cm −2 at 800 °C.